INOVASI DIGITAL DALAM ADMINISTRASI NEGARA: MENUJU LAYANAN PUBLIK YANG LEBIH EFISIEN DAN TRANSPARAN - Loso Judijanto; Melyana R Pugu (CV. Adiba Aisha Amira, 2024)
Digital transformation has become an important focus for state administration to improve public services. Digital innovation has the potential to simplify government procedures, increase citizens' access to information, and enable more open and transparent government. This study explores various aspects of digital innovation in the context of state administration and how they contribute to the more efficient provision of public services. Through literature analysis, this study identifies the successes, challenges, and best strategies in implementing digital technology. The results show that despite infrastructure barriers, cyber resilience, and the need for human resource capacity building, the move towards digital-based services can improve compliance, increase transparency, and reduce corruption. This study provides recommendations on how the government can adopt a policy framework and cross-sectoral collaboration that will accelerate the adoption of digital innovation, as well as how to mitigate risks related to data privacy and security